Rehabilitation for Femoroacetabular Impingement: Conservative Care and Postoperative Practice - Hagen, Mia S.; Westermann, Robert W.; Lynch, T. Sean; Rosneck, James (The Journal of Hip Surgery, 2018)
The understanding of femoroacetabular impingement (FAI) has increased over the past 10 years, with advancements in diagnosis and surgical techniques. Controversy remains regarding the ideal regimen of conservative care. Additionally, there is wide variety in postoperative clinical practice after hip arthroscopy. This review is a synthesis of resources on rehabilitation as a stand-alone treatment for FAI as well rehabilitation following surgery. Best evidence regarding conservative care is presented followed by postoperative debates on weight-bearing, range of motion, and physical therapy. In most cases, such as use of bracing and continuous passive motion, there are limited experimental studies to rely on. Higher quality evidence is required to support today's rehabilitation practices which are based mostly on theory and individual experience.
Keywords: hip arthroscopy; physical therapy; bracing; femoroacetabular impingement; weight-bearing